Draft Model of Support on the Labour Market Offered to Young People at Risk of Social Exclusion - Evaluation of Results - Kryk, Barbara (Studia Oeconomica Posnaniensia, 2015)
Reducing unemployment as well as increasing indicators of labour activity and social inclusion requires support from different groups that are faced with a difficult situation on the labour market. One such group is young people at risk of social exclusion. Within the framework of the project entitled "Adulthood, Self-reliance, Job" (implemented as part of the Social Capital Operational Programme 2007-2013), an innovative model of support has been developed to help young people find employment. The model has already been tested and evaluated in order to analyze its effects up to now and to assess the final result. The paper is a synthetic presentation of the evaluation results that are a basis for developing and improving the proposed model before it is implemented on a large scale. The article refers to the available documents and reports on the project under consideration